EFEKTIVITAS METODE SQRQCQ DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA ANAK BERKESULITAN BELAJAR - OVITRI YUNDASARI (Jurnal Penelitian Pendidikan Khusus, 2015)
AbstractThe research which started from the findings of a child can't finish the story operating calculating mixture of SDN 14 the koto Lalang Padang. A method of SQRQCQ is one method used to improve the ability to resolve child story about a mixture of operation count, the purpose of this research is to prove the effectiveness of a method of SQRQCQ in improving the ability to finish the operation of a story about a mixture of in count berkesulitan children learn at SDN 14 the koto lalang Padang .    Keyword: SQRQCQ method, solving story, learning disability